Congenital Deafness and Recent Advances Towards Restoring Hearing Loss. Issue 3 (29th March 2021) - Renauld, Justine M.; Basch, Martin L.
Abstract: Congenital hearing loss is the most common birth defect, estimated to affect 2‐3 in every 1000 births. Currently there is no cure for hearing loss. Treatment options are limited to hearing aids for mild and moderate cases, and cochlear implants for severe and profound hearing loss. Here we provide a literature overview of the environmental and genetic causes of congenital hearing loss, common animal models and methods used for hearing research, as well as recent advances towards developing therapies to treat congenital deafness. © 2021 The Authors.